2004
DOI: 10.1097/01.aog.0000137349.79204.b8
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Adverse Effects Associated With Raloxifene: Multiple Outcomes of Raloxifene Evaluation

Abstract: I

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
72
4
5

Year Published

2005
2005
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(91 citation statements)
references
References 31 publications
10
72
4
5
Order By: Relevance
“…Overall, the incidences of AEs, serious AEs, and discontinuations due to AEs with bazedoxifene were not different from those (14)(15)(16)(17) ; however, this study found no significant differences in the incidence of hot flushes between the bazedoxifene and placebo treatment groups. This finding is consistent with the low incidence of hot flushes seen with raloxifene in postmenopausal Japanese women (11) and reports that Asian women are generally less likely to report hot flushes and other menopausal symptoms than white women.…”
Section: Discussioncontrasting
confidence: 68%
“…Overall, the incidences of AEs, serious AEs, and discontinuations due to AEs with bazedoxifene were not different from those (14)(15)(16)(17) ; however, this study found no significant differences in the incidence of hot flushes between the bazedoxifene and placebo treatment groups. This finding is consistent with the low incidence of hot flushes seen with raloxifene in postmenopausal Japanese women (11) and reports that Asian women are generally less likely to report hot flushes and other menopausal symptoms than white women.…”
Section: Discussioncontrasting
confidence: 68%
“…15 R has not been linked to cataract formation. 12,14,16 Results from the present study using RhREC show that E2 induced a reduction of the level of VEGF and PEDF. Suzuma and colleagues 25 reported an increase of VEGF in response to E2 treatment of bovine retinal endothelial cells, and Mueller and colleagues 28 reported an increase in VEGF in human endometrial cells in response to E2.…”
Section: Discussionmentioning
confidence: 54%
“…15 Investigation of R at 60 or 120 mg/day compared to placebo in a study of 7,705 women for a mean of 3.3 years has demonstrated no increased risk of cataract. 16 The updated STAR report demonstrated a slightly higher risk of invasive breast cancer with R when compared to T, but once again revealed an enhanced safety profile with R as was demonstrated in the first study. R was reported to maintain 76% of the effectiveness of T, which correlates to a 38% reduction in invasive breast cancer compared to no treatment.…”
mentioning
confidence: 80%
“…Raloxifene increases the risk of VTE similarly to what has been observed with tamoxifen and E use in postmenopausal women (4,(12)(13)(14). In the Multiple Outcomes of Raloxifene Evaluation (MORE) trial, the risk of venous thromboembolic disease (deep venous thrombosis or pulmonary embolism) was found to be 3.1 times higher (95% confidence interval, 1.5 to 6.2) in women assigned to the raloxifene group than to the placebo group.…”
Section: Discussionmentioning
confidence: 74%